Social Discrimination in Jane Austen's Sense and Sensibility(1811):A Marxist Approach - Fathoni, Ahmad; , Drs. Abdillah Nugroho, M.Hum; , Titis Setyabudi, S.S, M.Hum (2015)
The study is aimed to show the struggle of Elinor Dashwood and Marianne Dashwood to get prosperity. The object of the study of this research is to analyze the novel based on its structural elements and the struggle of Elinor Dashwood and Marianne Dashwood in order to get prosperity using a Marxist Approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is taken from the novel Sense and Sensibility written by Jane Austen in 1811. While secondary data sources are other material taken from library books, criticism, essay, articles, journal and internet related to the study. Both data are collected through library reseach and analyzed by descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis, it shows that the character and characterization, setting, plot, style and theme of the novel are related into solid unity. Secondly, based on Marxist analysis the novel tells that in order to get prosperity the major charater Elinor Dashwood and Marianne Dashwood have to trough several conflict those are: cultural conflict and social conflict. Then, after overcoming those conflict Elinor Dashwood and Marianne Dashwood finnaly found what they are looking for and live happily.